Engaging EFL Learners with Mobile Instant Voice Messaging-based Speaking Activities: A Practice-based Qualitative Research - Falah, Mohammad Nur; Margiyanti, Dwi Arni Siti; Prayogo, Agus ((JELE) Journal Of English Language and Education, 2021)
This study explored EFL learners' engagement in English speaking activities employing mobile instant voice messaging applications such as WhatsApp at a secondary education level. Designed as a practice-based qualitative research, the study was conducted among 32 EFL learners working in a direct conversation of speaking practice in a WhatsApp group. The participants’ voice messages were observed as four of them were involved in follow-up interviews which were then qualitatively analyzed. The findings show that speaking activities facilitated with mobile instant voice messaging reveal that students typically can engage in practically easy speaking activities, give more time and space to practice, and helps them to speak confidently. The platform has also facilitated students through an accessible technological tool with useful features for various online speaking class activities and provided chance to reach the application with different needs and backgrounds. In this sense, those facts related to the students’ engagement in speaking class imply a recommendation for EFL speaking classrooms that respond to the current condition and trend.